Everything you ever needed to know about training : a complete step-by-step guide to training and development / Kaye Thorne, David Mackey - Thorne, Kaye (Kogan page, 2001)
This comprehensive guide to training covers everything from designing, delivering and evaluating training to advice on training as a career and advice on the use (and misuse) of online training, Intrancts and the Internet. An ideal hand-holding guide for those new to training or wanting to develop their training skills, the book also includes valuable advice for trainers on training as a business and going it alone. Complete with a detailed appendix listing useful names, addresses, contact points and websites this practical handbook that proved itself invaluable in its first edition is now dotcom compliant!